Reform of Quota and Voice in the International Monetary Fund-Draft Report of the Executive Board to the Board of Governors. (Policy Papers; Policy Paper ;, 2008)
This report sets out a proposal for a second-round package of reforms consistent with the framework agreed in the Singapore Resolution and, to that end, recommends that the Board of Governors approve the resolution that is appended to this Report (the "Resolution").